Role of alginate in infection with mucoid Pseudomonas aeruginosa in cystic fibrosis. Issue 1 (January 1992) - Pedersen, S S; Høiby, N; Espersen, F; Koch, C
Abstract : BACKGROUND: Chronic bronchopulmonary infection with mucoid, alginate producing Pseudomonas aeruginosa occurs characteristically in patients with cystic fibrosis. Alginate may be a virulence factor for P aeruginosa infection in such patients. METHODS: Forced vital capacity (FVC), nutritional state and the antibody response to P aeruginosa were determined at regular intervals from three years before chronic P aeruginosa infection to 10 years afterwards in 73 patients with cystic fibrosis. All patients were treated intensively with antipseudomonal chemotherapy during the study period. RESULTS: FVC was reduced in all patients who subsequently developed P aeruginosa infection before they acquired the infection, indicating significant pre-existing lung damage when compared with patients who remained free of P aeruginosa. Lung function and nutritional state remained unchanged after 10 years of infection, except in the patients who died of P aeruginosa lung infection. The FVC and height and weight of patients infected with nonmucoid strains of P aeruginosa were similar to those of uninfected patients. Patients infected with mucoid strains had poorer lung function and nutritional state for the first five years after infection compared with patients with nonmucoid strains. Such infection was also associated with greater IgG and IgA antibody responses to P aeruginosa standard antigen compared with nonmucoid infection. Concentrations of antibody to alginate were similar in patients with non-mucoid and mucoid infection. Noticeably increased concentrations of IgA antibodies to P aeruginosa standard antigen were observed early after the onset of infection in patients who subsequently died. CONCLUSION: Alginate producing P aeruginosa infection is associated with a hyperimmune response and poor clinical condition, suggesting that alginate production is a virulence factor in such infections in patients with cystic fibrosis.